2019
DOI: 10.1111/pcn.12921
|View full text |Cite
|
Sign up to set email alerts
|

Examination of retinal vascular trajectory in schizophrenia and bipolar disorder

Abstract: Aim: Evidence suggests microvascular dysfunction (wider retinal venules and narrower arterioles) in schizophrenia (SCZ) and bipolar disorder (BD). The vascular development is synchronous with neuronal development in the retina and brain. The retinal vessel trajectory is related to retinal nerve fiber layer thinning and cerebrovascular abnormalities in SCZ and BD and has not yet been examined. Hence, in this study we examined the retinal vascular trajectory in SCZ and BD in comparison with healthy volunteers (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 81 publications
1
16
0
Order By: Relevance
“…Because SZ and BD share the biological basis of psychoses [1][2][3][4][5][6][7][8][9][10][11][51][52][53][54][55][56][57] and they sometimes present similar pathologies, detection of anatomical and functional biomarkers that differentiate SZ and BD patients is crucial for the optimization of pharmacological and psychosocial treatments for each condition. The results of our ROC analyses suggest that the right hippocampal volume is a potential marker for differentiation between SZ and BD.…”
Section: Discussionmentioning
confidence: 99%
“…Because SZ and BD share the biological basis of psychoses [1][2][3][4][5][6][7][8][9][10][11][51][52][53][54][55][56][57] and they sometimes present similar pathologies, detection of anatomical and functional biomarkers that differentiate SZ and BD patients is crucial for the optimization of pharmacological and psychosocial treatments for each condition. The results of our ROC analyses suggest that the right hippocampal volume is a potential marker for differentiation between SZ and BD.…”
Section: Discussionmentioning
confidence: 99%
“…In BD, one study reported no significant difference between BD and HC, whereas another study reported narrowed arterioles and widened venules . Furthermore, another recent study reported that patients with BD had abnormal arteriolar or venular trajectories . Since metabolic problems are common in BD, current results might be confounded by metbolic abnormalities.…”
Section: Comparison Of the Retinal Measures And Growth Factor Levels mentioning
confidence: 76%
“…Studies show that telepsychiatry and AI can be effectively deployed for automated evaluation, namely imaging and behavior analysis, 47 evaluating biosignals, 48 assessing language use in mental disorders, 49 acoustic analysis, 50 knowledge-based methods, 51 and retinal examination. 52 56 Other potential uses include online information exchange and support services using social media and networking, 57 psychiatric consultation in primary care and emergency rooms, 58 and asynchronous psychotherapy. 59 Home care and related interventions for the geriatric population are also possible using technology.…”
Section: Discussionmentioning
confidence: 99%
“…Technological features include videoconference, telephone, and messaging systems, 61,62 web-based interactions, 63,64 mobile phone technologies, 65 networking via social media and group discussions, 66 simulated people and places, 67 and internet games. 68 The technology aspect of telepsychiatry has been experimented on a small scale in different cultural set- Retinal examination [52][53][54][55][56] Online information exchange and support services 57 Psychiatric consultation in primary care and emergency rooms 58 Asynchronous psychotherapy 59 Home care and related interventions 60 for ways to accommodate this online health-seeking behavior of their patients in their regular practice, beginning from the current pandemic, into the future.…”
Section: Technological Attributes Of Telepsychiatry and Aimentioning
confidence: 99%